2020
DOI: 10.1142/s2737416521500046
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Natural Curcumins and Related Compounds Against SARS-CoV-2

Abstract: The new coronavirus (COVID-19) is a viral disease that was classified as a pandemic situation on a global scale in early 2020. Severe Acute Respiratory Syndrome (SARS-CoV)-2 has the enzyme Mpro, until then, best characterized as an important biological target for intracellular viral replication. To investigate the interactions between curcumins and other compounds derived from cinnamic acid with the SARS-CoV-2 Mpro protease as well as to infer their physicochemical and drug-like properties, four natural curcum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The primary objective of the scientific community is to develop effective drugs. This objective needs a systematic limiting of pharmacological candidates, which is typically accomplished by virtual screening techniques [ 20 ]. In-silico drug screening employing several computer-aided drug design applications, the rational drug design process is substantially accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of the scientific community is to develop effective drugs. This objective needs a systematic limiting of pharmacological candidates, which is typically accomplished by virtual screening techniques [ 20 ]. In-silico drug screening employing several computer-aided drug design applications, the rational drug design process is substantially accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, baicalein and quercetin presented potential interactions with ACE2 receptor, by molecular docking, which can support its use in patients with severe COVID-19[ 21 ]. In this way, molecular docking studies have been used in screening of new substances that interact with SARS-CoV-2 proteins, as the Mpro, RdRp and PLpro[ 15 , 16 , [22] , [23] , [24] , [25] ]. For example, andrographolide from Andrographis paniculate presented a potential of Mpro inhibition, and other study showed that some flavonoids and indole-chalcones might impair SARS-CoV-2 infection and replication through enzymatic inhibition [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its hydrophobic core of M17 has a hydropathic index 1.9 demonstrating that this region attracts substances capable of crossing the PM. These compounds' cell invading ability further is explained by MLOGP evaluation (Table 1) (Alves et al, 2021;Moriguchi et al, 1992;Rocha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…After that, the files were uploaded and submitted to the web-based tool, SwissDock (http://www.swissdock.ch/docking#) (Webb & Sali, 2019), Swiss Institute of Bioinformatic (SIB) server, for molecular docking simulation. Subsequently, the results received were processed in the UCSF Chimera® software, for analysis and comparison of the distances and interactions of curcumins with the interaction amino acid residues of N3, Azithromycin(AZT), and Baricitinib(BRT) (Alves et al, 2021;Rocha et al, 2021). From the distances obtained, the data were computed and plotted on the web-based tool, Morpheus (https://software.broadinstitute.org/morpheus/), and heatmaps were used to visualize changes in the ligand-residue interaction profiles (L-R's), being evaluated by the Pearson statistical test to detect similarity.…”
Section: Methodsmentioning
confidence: 99%